Large remnant polarization and great reliability characteristics in W/HZO/W ferroelectric capacitors - Asapu, Shiva; Pagaduan, James Nicolas; Zhuo, Ye; Moon, Taehwan; Midya, Rivu; Gao, Dawei; Lee, Jungmin; Wu, Qing; Barnell, Mark; Ganguli, Sabyasachi; Katsumata, Reika; Chen, Yong; et al. (Frontiers in Materials, 2022)
In this work, the effect of rapid thermal annealing (RTA) temperature on the ferroelectric polarization in zirconium-doped hafnium oxide (HZO) was studied. To maximize remnant polarization (2Pr), in-plane tensile stress was induced by tungsten electrodes under optimal RTA temperatures. We observed an increase in 2Pr with RTA temperature, likely due to an increase of the polar ferroelectric phase in HZO. The HZO capacitors annealed at 400°C did not exhibit any ferroelectric behavior, whereas the HZO capacitors annealed at 800°C became highly leaky and shorted for voltages above 1V. On the other hand, annealing at 700°C produced HZO capacitors with a record-high 2Pr of ∼64μCcm^−2 at a relatively high frequency of 111kHz. These ferroelectric capacitors have also demonstrated great endurance and retention characteristics, which will benefit neuromorphic computing applications.